The Concept of Bodhisattva as a Ground of Social and Political Philosophy - Samacari (Luangkan), Pharama Somjet (Mahachula Academic Journal, 2021)
This dissertation entitled ‘An Analytical Study of the Concept of Buddha-nature in Buddhist Philosophy’ has three objectives: (1) to study the concept of Buddha-nature in Theravada Buddhist philosophy, (2) to study the concept of Buddha-nature in Mahayana Buddhist philosophy, and (3) to analyze the concept of Buddha-nature in Theravada Buddhist philosophy and Mahayana Buddhist philosophy. This is a documentary research. The objective of this study, it was to found that The concept of Bodhisattva can be taken as the Ground of philosophy, social and political research methodology. In the Studies from the scripture, the Tripitaka and books relevant study results found that: Social and political philosophy discusses the problems arising from the Human rights and justice and equality of individuals in society are complicated As well as the relationship of people in society, so it's complicated as well. In a society so there will be parents as authorised users. Who received from members of the public offering to act as parents to keep the social peace. But when the parents had no moral will cause problems in social. The concept of the Bodhisattva is the focus to help human animal from suffering with compassion. Have a strong commitment to help Human and animals cross the Samsara, The source of suffering. With such features, it can be the foundation of social and political philosophy as well.